Fluid type influences acute hydration and muscle performance recovery in human subjects - Harris, Preston R.; Keen, Douglas A.; Constantopoulos, Eleni; Weninger, Savanna N.; Hines, Eric; Koppinger, Matthew P.; Khalpey, Zain I.; Konhilas, John P. (Journal of the International Society of Sports Nutrition, 2019)
Exercise and heat trigger dehydration and an increase in extracellular fluid osmolality, leading to deficits in exercise performance and thermoregulation. Evidence from previous studies supports the potential for deep-ocean mineral water to improve recovery of exercise performance post-exercise. We therefore wished to determine whether acute rehydration and muscle strength recovery was enhanced by deep-ocean mineral water following a dehydrating exercise, compared to a sports drink or mountain spring water. We hypothesized that muscle strength would decrease as a result of dehydrating exercise, and that recovery of muscle strength and hydration would depend on the type of rehydrating fluid. Using a counterbalanced, crossover study design, female (n = 8) and male (n = 9) participants performed a dehydrating exercise protocol under heat stress until achieving 3% body mass loss. Participants rehydrated with either deep-ocean mineral water (Deep), mountain spring water (Spring), or a carbohydrate-based sports drink (Sports) at a volume equal to the volume of fluid loss. We measured relative hydration using salivary osmolality (S ) and muscle strength using peak torque from a leg extension maneuver. S significantly increased (p < 0.0001) with loss of body mass during the dehydrating exercise protocol. Males took less time (90.0 ± 18.3 min; P < 0.0034) to reach 3% body mass loss when compared to females (127.1 ± 20.0 min). We used a mono-exponential model to fit the return of S to baseline values during the rehydrating phase. Whether fitting stimulated or unstimulated S , male and female participants receiving Deep as the hydrating fluid exhibited the most rapid return to baseline S (p < 0.0001) regardless of the fit parameter. Males compared to females generated more peak torque (p = 0.0005) at baseline (308.3 ± 56.7 Nm vs 172.8 ± 40.8 Nm, respectively) and immediately following 3% body mass loss (276.3 ± 39.5 Nm vs 153.5 ± 35.9 Nm). Participants experienced a loss. We also identified a significant effect of rehydrating fluid and sex on post-rehydration peak torque (p < 0.0117). We conclude that deep-ocean mineral water positively affected hydration recovery after dehydrating exercise, and that it may also be beneficial for muscle strength recovery, although this, as well as the influence of sex, needs to be further examined by future research. clincialtrials.gov PRS, NCT02486224 . Registered 08 June 2015.